Adenomatoid odontgenic tumor - Torresyap, Vincent P. (The Journal of the Philippine Dental Association)
Adenomatoid Odontogenic Tumor is a slow growing lesion that occurs most often between 5 to 30 years of age. Odontogenic tumors are lesions derived from epithelial or mesenchymal elements of the tooth-forming cells. In most cases, this appears during the second decade with females more commonly affected compared to males. This case report involves an 11 years old male patient complaining of recurrent swelling on the left side of the face and its management.